2017
DOI: 10.1002/ajh.24922
|View full text |Cite
|
Sign up to set email alerts
|

Residual disease detection using targeted parallel sequencing predicts relapse in cytogenetically normal acute myeloid leukemia

Abstract: Despite achieving complete remission after intensive therapy, most patients with cytogenetically normal (CN) AML relapse due to the persistence of submicroscopic residual disease. In this pilot study, we hypothesized that detection of leukemia-specific mutations following consolidation treatment using a targeted parallel sequencing approach predicts relapse. We included 34 AML patients of whom diagnostic material and remission bone marrow slides after at least one cycle of consolidation were available. Isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
(55 reference statements)
3
18
0
Order By: Relevance
“…15 Recently, clearance of mutations <0.5% and 0.01% (using deep sequencing and droplet digital PCR, respectively) was shown to be associated with decreased risk of relapse. 17,18 Morita et al 47 reported significantly better 2-year overall survival for AML patients with mutation clearance VAF <1% as well as complete mutation clearance in complete remission, but not if the VAF of residual mutations was <2.5%. The combined use of MFC-MRD and mutation clearance in complete remission was shown by Jongen-Lavrencic et al 48 to confer additive prognostic value for relapse rate and overall survival compared with either method alone.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, clearance of mutations <0.5% and 0.01% (using deep sequencing and droplet digital PCR, respectively) was shown to be associated with decreased risk of relapse. 17,18 Morita et al 47 reported significantly better 2-year overall survival for AML patients with mutation clearance VAF <1% as well as complete mutation clearance in complete remission, but not if the VAF of residual mutations was <2.5%. The combined use of MFC-MRD and mutation clearance in complete remission was shown by Jongen-Lavrencic et al 48 to confer additive prognostic value for relapse rate and overall survival compared with either method alone.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies utilizing NGS for the detection of MRD in AML vary greatly in their design and technical aspects. Cohorts studied have included AML patients undergoing allogeneic haematopoietic cell transplantation (alloHCT) (Getta et al , ; Kim et al , ; Thol et al , ; Zhou et al , ; Press et al , ), receiving standard induction chemotherapy (Klco et al , ; Gaksch et al , ; Jongen‐Lavrencic et al , ; Morita et al , ; Onecha et al , ; Rothenberg‐Thurley et al , ; Thol et al , ; Wong et al , ), receiving novel therapies in clinical trials (Levis et al , ), or having only specific mutations (Thol et al , ; Kohlmann et al , ; Salipante et al , ; Levis et al , ; Patkar et al , ; Zhou et al , ; Patel et al , ). Also, since most studies to date have had access to diagnostic samples, de novo leukaemia‐associated mutation discovery using remission samples alone remains an important unmet challenge.…”
Section: Current State Of Ngs Mrd Detection In Amlmentioning
confidence: 99%
“…were analyzed by dPCR as described. 20 In brief, after DNA extraction using the QIAamp DNA Micro Kit (Qiagen, Hilden, Germany) dPCR was performed in duplicates using QuantStudio 3D Master Mix v2 and a QuantStudio 3D Digital PCR System (Applied Biosystems).…”
Section: Detection Of the Npm1 W288fs*12 Mutation By Digital Pcr (Dmentioning
confidence: 99%
“…Sequencing of other mutations was done using an Ion Torrent platform as described. 20 as competing risk. 9 The Fine and Gray model was used for univariate and multivariate assessment of risk factors for relapse using cmprisk 2.2-8.…”
Section: Mutational Analysis By Ngsmentioning
confidence: 99%